1990
DOI: 10.1007/bf00187319
|View full text |Cite
|
Sign up to set email alerts
|

Light-evoked walking in crayfish: Behavioral and neuronal responses triggered by the caudal photoreceptor

Abstract: The caudal photoreceptors (CPRs) of crayfish (Procambarus clarkii) can trigger walking and abdominal movements by their response to light.1. In a restrained, inverted crayfish, illumination of A6 evoked a CPR discharge followed by leg movements and bursting from the abdominal tonic flexor (TF) motoneurons. Intracellular electrical stimulation of a single CPR at high frequency (80 Hz) evoked similar responses.2. Responses only occurred when a single CPR axon was driven at 60 Hz or more and outlasted the stimulu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 37 publications
2
34
0
Order By: Relevance
“…Photoresponses in the segmental nerves have been reported in the crayfish and the swallowtail butterfly. In the crayfish, illumination of the terminal abdominal ganglion evokes a cyclic firing pattern from the abdominal tonic flexor motor neurons, as recorded from the nerve roots (Edwards, 1984;Simon and Edwards, 1990). Spontaneous discharges were recorded in the dark from the sixth peripheral nerve of the terminal abdominal ganglion of the butterfly, and the frequency of some impulses was enhanced or inhibited upon direct illumination of the ganglion (Arikawa et al ., 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Photoresponses in the segmental nerves have been reported in the crayfish and the swallowtail butterfly. In the crayfish, illumination of the terminal abdominal ganglion evokes a cyclic firing pattern from the abdominal tonic flexor motor neurons, as recorded from the nerve roots (Edwards, 1984;Simon and Edwards, 1990). Spontaneous discharges were recorded in the dark from the sixth peripheral nerve of the terminal abdominal ganglion of the butterfly, and the frequency of some impulses was enhanced or inhibited upon direct illumination of the ganglion (Arikawa et al ., 1991).…”
Section: Discussionmentioning
confidence: 99%
“…The CPR neurons depolarise upon photic stimulation of the ganglion, but do not adapt over time (291,292). The neuroanatomy of these cells has been detailed to some extent (291,(293)(294)(295), but full morphological details such as final projection sites and terminal connectivities have not been fully resolved. Some additional interneurons located in more anterior abdominal ganglia have been described as photosensitive, but their neuroanatomy and physiological functions are not understood (291).…”
Section: The Caudal Photoreceptor Of the Crayfish Terminal Abdominal mentioning
confidence: 99%
“…2000 lux for 10-30min), the CPR initiates phase shifts in locomotory (296,303) and ERG rhythms (84,298). In the cases of its effects on the ERG and the size of the pseudopupil (87), the CPR most likely feeds sensory information into more anteriorly located pacemaker systems via the ascending projections running through the entire VNC into the brain (293), although the postsynaptic interneuronal targets have not been identified (12).…”
Section: Integration Of Distributed Circadian Clock Systems and Rhythmentioning
confidence: 99%
“…In addition, the previous studies demonstrated that the caudal photoreceptor of crayfish could trigger walking by their response to light stimulation [60][61][62]. In our experiments under the LD condition (Fig.…”
Section: Effects Of Retinal and Extraretinal Input On The Circadian Rmentioning
confidence: 54%